How Does Perceived Support for Innovation Lead to Deviant Innovation Behavior of Knowledge Workers? A Moderated Mediation Framework - Yuan, Shujie; Liu, Xuan (Frontiers in Psychology, 2022)
Many studies concerning deviant innovation behavior mainly focus on the influence of personality differences or leadership styles, and there is a lack of attention given to internal cognitive factors related to actors. Therefore, the purpose of this paper is to examine the internal mechanism of perceived support for innovation on deviant innovation behavior. A two-wave study was conducted among 393 knowledge workers from 10 knowledge-intensive enterprises in the People's Republic of China. Model 4 and Model 14 from SPSS macro PROCESS are used to test the mediating effect of innovation commitment and the moderating effect of threatened self-identity, respectively. The findings suggest that perceived support for innovation can significantly predict deviant innovation behavior; innovation commitment fully mediates the relationship between perceived support for innovation and deviant innovation behavior; public threat to self-identity plays a moderating role in the relationship between innovation commitment and deviant innovation behavior; and public threat to self-identity moderates the mediating effect of innovation commitment on perceived support for innovation and deviant innovation behavior. This study enriches the research on antecedent variables of deviant innovation behavior, and highlights the important role of situational factors on the whole mechanism.